Growth Hormone(s), Testosterone, Insulin-Like Growth Factors, and Cortisol: Roles and Integration for Cellular Development and Growth With Exercise - Kraemer, William J.; Ratamess, Nicholas A.; Hymer, Wesley C.; Nindl, Bradley C.; Fragala, Maren S. (Frontiers in Endocrinology, 2020)
Hormones are largely responsible for the integrated communication of several physiological systems responsible for modulating cellular growth and development. Although the specific hormonal influence must be considered within the context of the entire endocrine system and its relationship with other physiological systems, three key hormones are considered the “anabolic giants” in cellular growth and repair: testosterone, the growth hormone superfamily, and the insulin-like growth factor (IGF) superfamily. In addition to these anabolic hormones, glucocorticoids, mainly cortisol must also be considered because of to their profound opposing influence on human skeletal muscle anabolism in many instances. This review presents emerging research on: 1) Testosterone signaling pathways, responses, and adaptations to resistance training; 2) Growth hormone: presents new complexity with exercise stress; 3) Current perspectives on IGF-I and physiological adaptations and complexity of this superfamily as related to training; and 4) Glucocorticoid roles in integrated communication for anabolic/catabolic signaling. Specifically, the review describes 1) Testosterone is the primary anabolic hormone, with an anabolic influence largely dictated primarily by genomic and possible non-genomic signaling, satellite cell activation, interaction with other anabolic signaling pathways, upregulation or downregulation of the androgen receptor, and potential roles in co-activators and transcriptional activity; 2) Differential influences growth hormones depending on the “type” of the hormone being assayed and the magnitude of the physiological stress; 3. The exquisite regulation of IGF-1 by a family of binding proteins (IGFBPs 1–6), which can either stimulate or inhibit biological action depending on binding; and 4) Circadian patterning and newly discovered variants of glucocorticoid isoforms largely dictating glucocorticoid sensitivity and catabolic, muscle sparing, or pathological influence. The downstream integrated anabolic and catabolic mechanisms of these hormones not only affect the ability of skeletal muscle to generate force; they also have implications for pharmaceutical treatments, aging, and prevalent chronic conditions such as metabolic syndrome, insulin resistance, and hypertension. Thus, advances in our understanding of hormones that impact anabolic: catabolic processes have relevance for athletes and the general population, alike.